The Extent of Implementing the School’s Development Plan from the Point of View of Supervisors - Ali Mohammed, Jassim; Q. Mohammad, Mohammad; Abbood Muhaibs, Abdulameer (International Journal of Psychosocial Rehabilitation, 2020)
Educational systems in all Arab countries seek to improve performance, and for this purpose they aim to liberate schools from the hegemony of the central pattern in planning and management, a pattern that has prevailed for decades because of the political and economic conditions in the world. Passed The decentralized approach to school planning and management is consistent with the nature of the transformation that Arab societies have witnessed for a while, especially in our country, Iraq, where the goal has become to expand the area of responsibility in performance evaluation, to see the extent of development in performance, and to discover glitches so that quick solutions can be found.